China and Latecomer Industrialization Processes in Sub-Saharan Africa: A Case of Combined and Uneven Development. (1st July 2016) - ,
Abstract : This article examines the question of how China's systemic impact on the world economy and growing presence in sub-Saharan Africa (SSA) affects processes of structural change in SSA countries through the framework of combined and uneven development: Global economic forces can act to perpetuate underdevelopment, but these global forces, of which China's rise in the world economy is one among many, need to be studied in conjunction with the societal forces that mediate them. This article argues that many China-related effects actually work in favor of manufacturing development, but the size and composition of China-related effects vary considerably across countries. Therefore, the article uses cluster analysis to find groups of SSA countries with similar patterns of interaction with China and shows that we do, indeed, observe differences in average manufacturing output growth across these groups. However, the cluster analysis also reveals considerable variations within the groups of countries with similar China-related effects. The article provides a case study on Angola to illustrate the interplay between global factors linked to China and the domestic political economy setting.